Apartheid guns and money a tale of profit - Van Vuuren, Hennie (Auckland Park Jacana, 2017)
In its last decades, the apartheid regime was confronted with an existential threat. While internal resistance to the last whites-only government grew, mandatory international sanctions prohibited sales of strategic goods and arms to South Africa. To counter this, a global covert network of nearly fifty countries was built. In complete secrecy, allies in corporations, banks, governments and intelligence agencies across the world helped illegally supply guns and move cash in one of history's biggest money laundering schemes. Whistleblowers were assassinated and ordinary people suffered.
Includes bibliographical references and index
Keywords: Apartheid--South Africa